Semantic Playlist Engineering: A Conceptual Approach to Digital Content Organization through Semantic Domains - Fardiansyah Fardiansyah; Anhar Anhar; Sepri Kurniadi (PERFECT: Journal of Smart Algorithms, 2026)
The rapid growth of digital content enabled by Generative Artificial Intelligence (Generative AI) has shifted the primary challenge for creators from content production to the organization of continuously expanding digital collections. Existing content organization mechanisms, such as playlists, albums, and collections, are commonly based on technical characteristics including genre, publication chronology, or media type, making them less effective in representing the conceptual relationships among creative works. Meanwhile, semantic approaches reported in previous studies have primarily focused on recommendation systems, information retrieval, metadata enhancement, and automatic playlist generation rather than creator-centric content organization.This study introduces Semantic Playlist Engineering (SPE) as a conceptual approach to digital content organization through Semantic Domains. Within the proposed approach, a Semantic Domain is defined as a conceptual space that groups creative works sharing similar meanings regardless of their technical characteristics or platform implementation. These domains are subsequently represented through Semantic Playlist Organization (SPO), allowing platform-specific organizational mechanisms such as playlists, collections, albums, or series to serve as representations of semantic organization.The study adopts a conceptual descriptive research approach supported by a case study involving digital music produced by Studio Isi Pundi Sound™ and published through the FartressMusic YouTube channel. The case study demonstrates how semantically related creative works can be organized into illustrative Semantic Domains to support coherent creator-centric content organization.The primary contribution of this study is the introduction of Semantic Playlist Engineering, Semantic Domains, and Semantic Playlist Organization as a unified conceptual foundation for organizing creator-owned digital content. Rather than proposing a recommendation algorithm or an automated classification model, this study offers a new perspective that positions semantic meaning as the principal basis for long-term digital content organization across different digital platforms.